2020
DOI: 10.13106/jafeb.2020.vol7.no6.265
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ Remuneration and Performance: Evidence from the Textile Sector of Bangladesh

Abstract: This study investigates the impact of board incentives as proxied by directors` remuneration on the financial performance of listed textile companies in Bangladesh. Using Generalized Method of Moments (GMM) and data pertaining to listed textile companies of Dhaka Stock Exchange (DSE) during the period from 2011 to 2017 (resulting in a total of 140 firm-year observations), we have estimated the firm performance equation involving directors' remuneration and board independence as the independent variables and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Padia & Callaghan (2020; Harymawan et al, 2020) emphasized the important role of remuneration in increasing company performance. In addition, Lemma et al (2020) also found in South Africa companies, and Akter et al (2020) in Bangladesh companies, that remuneration does not have significant influence on company financial performance. A number of literatures provide different findings regarding the influence of remuneration.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Padia & Callaghan (2020; Harymawan et al, 2020) emphasized the important role of remuneration in increasing company performance. In addition, Lemma et al (2020) also found in South Africa companies, and Akter et al (2020) in Bangladesh companies, that remuneration does not have significant influence on company financial performance. A number of literatures provide different findings regarding the influence of remuneration.…”
Section: Literature Reviewmentioning
confidence: 95%
“…While Latif et al (2020) document a positive relationship between non-executive directors on the board and firm performance, Amin and Nor (2019) report a negative relationship between the two variables. Moreover, Akter et al (2020), Combs et al (2007), and Le et al (2006) document an insignificant impact of independent and outside board members on firm performance. Furthermore, Majeed et al (2020) find that board composition, as measured by the proportion of non-executive directors to total board members, is significantly and negatively associated with ROA, but insignificantly related to ROE for Pakistani banking sector.…”
Section: Board Composition and Firm Performancementioning
confidence: 98%
“…Consistent with this study, Brick et al [58] and Haron [59] identified a poor positive connection between the board remuneration and performance. Brick et al [58] and Akter et al [17] also sustained that an excess in board remuneration generated underperforming outcomes of the companies due to weak or lack of corporate governance control.…”
Section: The Relationship Between Board Compensation Corporate Sustamentioning
confidence: 98%
“…Therefore, given the results obtained and debatable underpinnings on this subject, our paper contributes with several components to the literature. First, it brings new insights on the board compensation and structure, on one hand, and companies' performances, on the other hand, in synergy with CG and CSR for various European industries (most of previous research being focused either on a specific industry, like tourism [15] banking [4,5,16], textile [17] or on specific European countries, like, Portugal [18], Germany [7], Norway and Sweden [19], the United Kingdom [20] or Italy [21], while fewer papers have focused on a panel comprising many countries in Europe [12,22]). Second, based on updated data provided by the Thomson Reuters Eikon for 2019 and the first months of 2020 [14] from different countries, we will ensure the heterogeneity of variables included in the econometric analysis (especially, dependent variables) and the robustness of our findings.…”
Section: Introductionmentioning
confidence: 99%